Enhanced production of microalgal biomass and lipid as an environmentally friendly biodiesel feedstock through actinomycete co-culture in biogas digestate effluent - Kumsiri, Bancha; Pekkoh, Jeeraporn; Pathom-aree, Wasu; Lumyong, Saisamorn; Phinyo, Kittiya; Pumas, Chayakorn; Srinuanpan, Sirasit (Bioresource technology, 2021)
[Display omitted] •Actinomycete co-culture successfully enhanced both microalgal biomass and lipid.•Piscicocus intestinalis WA3 produced high algal growth-promoting agents.•Microbial lipids are composed of C16-C20 fatty acids with good fuel properties.•Biogas effluent can be used as cost-effective media for actinomycete co-culture. In this study, an innovative approach to enhance the production of microalgal biomass and lipid as a promising sustainable feedstock for biodiesel was proposed using an actinomycetes co-culture with microalgae in the biogas digestate effluent (BDE) that can be employed as an environmentally friendly and cost-effective strategy. Among tested actinomycete isolates, Piscicocus intestinalis WA3 produced indole-3-acetic acid and siderophores as algal growth promoting agents and showed effective lipid accumulation with satisfying fatty acids composition. During co-cultivation of P. intestinalis WA3 with microalga Tetradesmus obliquus AARL G022 in the BDE, biomass production, chlorophyll a content, and lipid productivity were significantly increased by 1.30 folds, 1.39 folds, and 1.55 folds, respectively, compared to microalgae monoculture. The accumulated lipids contained long-chain fatty acids with better fuel properties that could potentially be used as biodiesel feedstock. The overall results evidenced that actinomycete co-culture would contribute greatly to the cost-effective production of environmental-friendly microbial-based biofuel.